COMPARATIVE DEGREE OF THE STYLE DE VIDA OF THE ACADEMICS OF THE NOCTURNAL ONE OF PHYSICAL EDUCATION IN 2002/2006 (Fiep Bulletin - online, 2014)
The aspects of quality of life are influential agents in the individual profiles of the academics where if it becomes necessary to evidence a relation between the learning and the effective and conceptual professional exercise. This study it had as objective generality to verify the differences between the profile of the style of life of the year of signoff ingression and of the academics of the nocturnal course of the UNIVILLE. The used methods had broken of a bibliographical revision and a research of field with the pupils of the course of physical education/2002-2005. On 2002, 25 individuals had been selected (16 of masculine and nine feminine one) of 135 of the nocturnal group, the same ones had been selected for the after-test. Statistical used average and shunting line standard. The collected data had been: subcutaneous folds, stature, corporal weight, BMI, and Profile of the style of life (Nahas et al, 2000). With the gotten result the masculine group presented alterations in only one of the components of the profile of the life style, already the feminine group presented alterations in three of the components and in all the three presented a reduction of almost always for the times. On the relative conditions to the percent body fat in the generality, 13 citizens if had shown above of average and 12 below. Next to the percentage of corporal fat, already the Body Mass Indices of 22 citizens is in normal classification and two with on weight (moderately obese and another one severely obese). The results had demonstrated that the academics, exactly receiving pertinent information to an improvement from the life style, tend not to day-by-day make use of these information for its.
Keywords: Profile of the style of life; Health and quality of life; Academics